Remodelling of Mycobacterial Peptidoglycan During Cell Division and the Epigenetics of Macrophages during M. tuberculosis infection - Kieswetter, Nathan Scott (Institute of Infectious Disease and Molecular Medicine, 2021)
Tuberculosis (TB) has emerged as the world’s most deleterious infectious disease. The etiological agent of TB, Mycobacterium tuberculosis (Mtb), has evolved the ability to evade the host immune system using several mechanisms; emphasising the need for novel treatment strategies. Peptidoglycan (PG) is an important immunomodulatory heteropolysaccharide structure that can be shed during mycobacterial infection with immunological consequences and as such, changes in PG structure are expected to have important implications on disease progression and host responses. Mycobacterial amidases have been shown to have important roles in the remodelling of PG during cell division in M. smegmatis and are implicated in sensitivity to antibiotic treatment. However, their roles in modulating host immunity remain unknown. Herein, we assess the immune responses to Mtb mutants defective for either one of two amidases, Ami1 and Ami4, in bone marrow-derived macrophages (BMDM) and the C57BL/6 murine models of tuberculosis. Both Ami1 and Ami4 deletion resulted in increased pro-inflammatory response in BMDM. Infection with the Mtb Δami1 mutant in mice resulted in differential induction of proinflammatory cytokines and certain chemokines during the acute phase of the infection, an eff ect that was abrogated in chronic phase infection. The Δami1mutant was found to be susceptible to antibiotics in liquid growth culture but this sensitivity was negated in macrophages and reversed to a tolerant phenotype in mice. The Δami4 mutant, by contrast, did not display differential antibiotic susceptibility and did not significantly alter cytokine and chemokine responses relative to the wildtype control in mice. These findings suggest that Ami1 and Ami4 in Mtb play a nonoverlapping role in antibiotic sensitivity and modulating host immunity during tuberculosis. Additionally, the specific epigenetic alterations which occur during host-Mtb infection that contribute to immune evasion remain unknown. Here, we propose a method to elucidate transcriptomic changes in both human primary monocyte-derived macrophages (MDM) and the Mtb bacillus with which they were infected. In this study, we exhibit a dual-RNA-seq proof-of-concept methodology where, from a single donor, we successfully sequence host RNA from infected MDMs as well as Mtb RNA enriched from those same infected MDMs. Utilizing this optimised methodology, we aim to discover and model epigenetic and transcriptional alterations as well as their effector proteins in primary human macrophages following Mtb infection. Further, we aim to identify novel and annotated ncRNAs which are correlated with these epigenetic modifications.